Ketidakpatuhan Pembayaran Pajak Kendaraan Bermotor - Taofik Hidajat (EBBANK, 2018)
Motor Vehicle Tax is one of the most significant sources of income for developmentalfinancing in Central Java Province. However, the level of tax compliance by motor vehicle ownerswas not optimal. This research was conducted to determine the influencing factors of their uncompliance. The samples were 360 motor vehicle ownersdomiciled in Jepara, Blora, Grobogan, Kudus, Pati and Rembang and they still owned them  until the present. Through simple random sampling method applied during May to July 2017, the results indicated  that the cause of late tax payment in Pati was caused by two factors, both internally and externally. Some internal factors caused by tax payers itself namely forgetful and it was not done  by them in purpose. Second internal factors were done intentionally  (because of lacking  of funds, having no time, willingness to sell, rare use, old age,  damage , being out of town, being borrowed by other parties, absence of inspection on the road and being mortgaged. While some external factors were caused uncontrollable factors by  taxpayers namely far locations from home.